REPRESENTASI MASKULINITAS TOKOH UTAMA DALAM FILM LIVE ACTION TOKYO REVENGERS - Setiyadi, Akhmad; Noveri Faikar Urfan (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
This research was conducted with the aim of finding out and understanding how the representation of masculinity is visualized by the main character in the live action film Tokyo Revengers. In conducting the analysis, this research use Roland Barthes semiotic theory where the meaning process is divided into Denotation, Connotation and Myth which are associated with the concept of masculinity according to Janet Saltzman Chafetz which is divided into seven aspect. The research method used is Qualitative Descriptive by analyzing each scene that contains the masculine characteristics of the main character. The result obtained from this research show that the character Takemichi has seven concept of masculinity including: Aspect of male Physical Appearance, Male Fuctional, Male Sexual, Emotional, Intellectual, Male Interpersonal, and finally the Personal Character of man.